EVALUASI IMPLEMENTASI PROGRAM PENANAMAN DI KECAMATAN GUNUNGPATI OLEH MAHASISWA FAKULTAS ILMU SOSIAL - Subagyo, Subagyo; Ahmad, Tsabit Azinar (Indonesian Journal of Conservation, 2014)
The purposes of this research are as follows: (1) describing the implementation of planting in Gunungpati District done by students of Social Science Faculty of UNNES; (2) evaluating the implementation of planting in Gunungpati District done by students of Social Science Faculty of UNNES. The research activities were carried out in two Subdistric, Sekaran Subdistric and Plalangan Subdistric. Both Subdistrics were selected because they were the locations of planting done by students of Social Science Faculty of UNNES. This study was an evaluation. The Faculty of Social Sciences in 2012 did planting in Pongangan and Sekaran on a regular basis. Planting in the Sekaran Subdistric was conducted on March 18, 2012, then planting in Pongangan Subdistric was conducted on April 13, 2013. Planting in Sekaran area were conducted in three points, namely: (1) Margasatwa Street, Banaran; (2) Persen Village, and (3) Bandardowo Village RT II RW VII. There were 500 seedlings were planted. Planting in Pongangan Subdistric was also conducted in three points, namely in RW II, III RW, and RW V. The seeds planted reached 2060 seeds. The plants which were in well-maintained category were only 9% meanwhile the plants which were well-maintained were 40%. Last, the plants which categorized into bad condition were 51%. Then plants are not maintained in the category by 51%.Keywords: planting, conservation, studentTujuan penelitian dalam penelitian ini adalah sebagai berikut. (1) Mendeskripsikan implementasi penanaman di Kecamatan Gunungpati oleh mahasiswa Fakultas Ilmu Sosial Unnes; (2) Mengevaluasi implementasi penanaman di Kecamatan Gunungpati yang telah oleh mahasiswa Fakultas Ilmu Sosial Unnes. Lokasi kegiatan penelitian dilakukan di dua keluraan, yakni Kelurahan Plalangan dan Kelurahan Sekaran. Kedua kelurahan ini dipilih karena keduanya adalah lokasi penanaman yang dilakukan oleh mahasiswa Fakultas Ilmu Sosial Unnes. Penelitian ini merupakan penelitian evaluasi. Fakultas Ilmu Sosial pada tahun 2012 melakukan penanaman secara berkala di Kelurahan Pongangan dan Sekaran. Penanaman di Kelurahan Sekaran dilakukan pada tanggal 18 Maret 2012. Kemudian, penanaman di Pongangan dilakukan pada 13 April 2013. Penanaman di Sekaran dilakukan di tiga titik, yakni: (1) Jalan Margasatwa, Banaran; (2) Dukuh Persen, dan (3) Dukuh Bandardowo RT II RW VII. Di Kelurahan Sekaran, ditanam sebanyak 500 bibit. Penanaman di Pongangan dilakukan di tiga titik, yakni RW II, RW III, dan RW V. Penanaman di Kelurahan Pongangan mencapai 2060 bibit. Tanaman yang ada pada kategori terawat hanya 9 %. Sementara tanaman pada kategori terawat sebesar 40%. Kemudian tanaman yang berada pada kategori tidak terawat sebesar 51%.Kata kunci: penanaman, konservasi, mahasiswa